2017
DOI: 10.3233/jad-160820
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Occupational Therapy in Dementia Patients: Findings from a Real-World Observational Study

Abstract: OT may be an effective intervention to maintain cognition and functionality and to reduce psychiatric symptoms in dementia patients. Mild stages of dementia could gain more benefits from OT with regard to functional decline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 37 publications
1
15
0
1
Order By: Relevance
“…However, the service did not strictly conform to protocols formerly tested in randomized trials but rather drew on specific strategies and components that were then consistently and systematically delivered. Pre-post evaluation of the service showed maintenance of function over 3 months, stabilization of behaviors, and reductions in caregiver burden over 6 months, similar to previous trial findings ( Pimouguet, Le Goff, Wittwer, Dartigues, & Helmer, 2017 ).…”
supporting
confidence: 86%
“…However, the service did not strictly conform to protocols formerly tested in randomized trials but rather drew on specific strategies and components that were then consistently and systematically delivered. Pre-post evaluation of the service showed maintenance of function over 3 months, stabilization of behaviors, and reductions in caregiver burden over 6 months, similar to previous trial findings ( Pimouguet, Le Goff, Wittwer, Dartigues, & Helmer, 2017 ).…”
supporting
confidence: 86%
“…Patients are referred to ESA under medical prescription. We selected 10 ESA that were already involved in the pilot study (described elsewhere) and showed a high recruitment capacity [15]. Moreover, patients cared by these settings have been shown to be representative of the patients care by ESA at the national level [16].…”
Section: Methodsmentioning
confidence: 99%
“…The participants allocated to the control group benefit from the usual intervention described previously [15]. Briefly, patients referred to ESA followed a standardized treatment procedure consisting of 12 to 15 home sessions performed by a therapist over a period of 3/4 months focusing on patients and potential primary caregivers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The short-term efficacy of OT has been very recently investigated and ascertained in patients with dementia by Pimouguet et al (Pimouguet, Le Goff, Wittwer, Dartigues, & Helmer, 2017 (Pimouguet et al, 2017).…”
Section: Non-pharmacological Interventionsmentioning
confidence: 99%